2009
DOI: 10.1007/s11547-009-0397-3
|View full text |Cite
|
Sign up to set email alerts
|

Localized cervical cancer (stage <IIB): accuracy of MR imaging in planning less extensive surgery

Abstract: MR imaging had a high level of accuracy in the preoperative assessment of the extent of cervical tumour in patients eligible for conservative surgery. Accuracy is lower in the evaluation of the pelvic and lumboaortic lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…A meta-analysis of four studies carefully selected for IO involvement showed that the estimates of specificity and NPV were 91% and 99%, respectively 14 ; however, the four studies 1518 that were included in this analysis did not measure the actual distance of the tumour from the IO. 14 A recent retrospective study, 19 measured the distance from the IO on MRI and based the involvement of the IO on the patient's outcome (hysterectomy).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of four studies carefully selected for IO involvement showed that the estimates of specificity and NPV were 91% and 99%, respectively 14 ; however, the four studies 1518 that were included in this analysis did not measure the actual distance of the tumour from the IO. 14 A recent retrospective study, 19 measured the distance from the IO on MRI and based the involvement of the IO on the patient's outcome (hysterectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Nonostante ciò, le immagini morfologiche standard (immagini pesate in T1 e T2, con o senza la somministrazione di mezzo di contrasto) sono ancora necessarie per rispondere a specifi che domande, come il coinvolgimento dei parametri, dell'endocervice, dei fornici vaginali e dei linfonodi [29], come anche nel dare informazioni sul volume tumorale e sui dettagli anatomici dell'infi ltrazione di strutture adiacenti, soprattutto in pazienti candidate alla chirurgia e alla radioterapia [30].…”
Section: Discussionunclassified
“…Nevertheless, the usual morphological images (T2-and T1-weighted images, with or without administration of contrast medium) were still necessary to address specifi c questions, such as involvement of parametria, endocervix, vaginal fornices and lymph nodes [29], as well as to give information about tumour volume and anatomical details of infi ltration of adjacent structures in patients for whom surgery or radiotherapy is planned [30].…”
Section: Discussionmentioning
confidence: 99%
“…In stage IIB cervical cancer, MRI had 91% diagnostic accuracy, 67% sensitivity, and 92% specificity in assessing infiltration of the vaginal fornices, and 89% diagnostic accuracy, 28% sensitivity, and 100% specificity in the assessment of the lymph nodes, with a cutoff value of 1 cm 11. However, both CT and MRI cannot show the primary tumor’s metabolic characteristics, while FDG PET can provide information concerning the metabolic activity of a tissue region.…”
Section: Discussionmentioning
confidence: 99%